2019
DOI: 10.1590/1679-395174442x
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of smart cities and the internet of things as a research topic

Abstract: This study aims to analyze the current academic literature on Smart Cities and the Internet of Things using bibliometric analysis and quantitative content analysis. It primarily consists of extracting data from the web-of-science: citations, languages, countries, most prolific authors, the most relevant works, keywords, institutions, conferences, and journals. Results confirm that the most preeminent literature on Smart Cities and the Internet of Things focuses on developed countries with a long tradition of i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 48 publications
0
4
0
2
Order By: Relevance
“…This information demonstrated that the experts agreed that action was the step that was rated at the lowest level (mean = 4.67, SD = 0.62). In addition, the qualitative data from some experts has suggested calling these five learning processes 'the COSAS learning processes', where 'COSAS' is a Spanish word meaning 'things' (João, Souza, & Serralvo, 2020) that includes sensors, software and other technologies to connect and exchange data with smart devices via the Internet (Songsom, Nilsook, & Wannapiroon, 2019).…”
Section: Self-reflectionmentioning
confidence: 99%
“…This information demonstrated that the experts agreed that action was the step that was rated at the lowest level (mean = 4.67, SD = 0.62). In addition, the qualitative data from some experts has suggested calling these five learning processes 'the COSAS learning processes', where 'COSAS' is a Spanish word meaning 'things' (João, Souza, & Serralvo, 2020) that includes sensors, software and other technologies to connect and exchange data with smart devices via the Internet (Songsom, Nilsook, & Wannapiroon, 2019).…”
Section: Self-reflectionmentioning
confidence: 99%
“…According to incomplete statistics, 1000 cities can be identified around the world as having entered the path of intelligent development [3]. Despite growing interest and the publication of numerous studies), no clear conclusions can yet be drawn [9,[77][78][79][80][81][82][83][84][85][86] (approximately 200,000 articles [80] are written annually). Terms such as: "wired city", "ubiquitous city", "digital city", "smart communities", "intelligent city", "information city", "technocity" and "knowledge city" are often used interchangeably.…”
Section: The Concept Of the City Of The Future-the Smart Citymentioning
confidence: 99%
“…El desarrollo de estas variables tiene su funcionabilidad en gestionar ciudades basadas en el internet, destacándose que esta iniciativa ha figurado en los países que tradicionalmente han estado en la vanguardia tecnológica, investigación e innovación (Do-Nascimento-João, et al 2019), los autores brindan luces sobre la necesidad que se tiene en Latinoamérica de gestionar un acceso equitativo, de calidad, al internet, así como profundizar la investigación e innovación dentro del currículo educativo en todos sus niveles, especialmente en el universitario donde se hace pertinente diseñar un modelo integrador entre academia-industria con base a lo público-privado.…”
Section: Revolución 40 Y Educación Dualunclassified